1993
DOI: 10.1111/j.1749-6632.1993.tb49934.x
|View full text |Cite
|
Sign up to set email alerts
|

CRF and Related Peptides as Anti‐Inflammatory Agonistsa

Abstract: The permeability of endothelial surfaces increases in response to injury. We have shown that vascular leakage in experimental models of tissue injury can be inhibited by CRF and by a novel class of peptides that we call mystixins. Binding sites for iodinated-Tyro-CRF have been revealed in mucous membranes, and immunoreactive CRF-like materials have been found in inflamed tissues. Perhaps the breakdown of cytoskeletal intermediate filaments after insult generates or exposes peptide domains similar to mystixins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Local CRH injection into the hindpaw also inhibits inflammatory oedema formation (45). This is supported by several studies demonstrating that CRH administered into the periphery exerts anti‐inflammatory effects (46).…”
Section: Peripheral Crh As An Immunomodulatory Mediatormentioning
confidence: 58%
“…Local CRH injection into the hindpaw also inhibits inflammatory oedema formation (45). This is supported by several studies demonstrating that CRH administered into the periphery exerts anti‐inflammatory effects (46).…”
Section: Peripheral Crh As An Immunomodulatory Mediatormentioning
confidence: 58%
“…The most proximal component of both the central and peripheral HPA axis is CRH, which is expressed in combination with its receptors (CRH‐Rs) in human skin and on many immune cells, where it may have either pro‐ or anti‐inflammatory effects . There are conflicting reports on the expression of CRH and CRH‐R in psoriasis.…”
Section: Proposed Pathophysiology Of the Stress–psoriasis Associationmentioning
confidence: 99%
“…The most proximal component of both the central and peripheral HPA axis is CRH, which is expressed in combination with its receptors (CRH-Rs) in human skin 38 and on many immune cells, 39,40 where it may have either pro-or anti-inflammatory effects. [41][42][43][44] There are conflicting reports on the expression of CRH and CRH-R in psoriasis. Tagen et al 45 found reduced expression of CRH-R1 in affected skin and elevated serum CRH levels in patients compared with controls, while Zhou et al 46 found reduced CRH and CRH-R1 expression in involved skin compared with uninvolved and control skin.…”
Section: Hypothalamic-pituitary-adrenal Axis and Sympatheticadrenal-mmentioning
confidence: 99%
“…Several groups have noted heterogeneous forms of CRH‐ir in human immune tissues (3, 5, 15, 28) but little effort has been made to characterize these variant forms. In addition to reports that peripheral CRH can exert pro‐inflammatory actions, there is also evidence for anti‐inflammatory effects of CRH (33). These apparently conflicting reports may reflect differential degradation of CRH under different experimental conditions into fragments with their own selective activity.…”
Section: Discussionmentioning
confidence: 99%